Flowers increase ecosystem biodiversity in Midwestern prairies - Goodman, Lucas Michael; Debinski, Diane M; Lyon, Nicholas J (Journal of Student Research, 2018)
Loss of biodiversity due to anthropogenic factors, such as climate change and habitat conversion or loss, is among the largest problems affecting many native ecosystems today. Declines in plant diversity can often have detrimental effects on other forms of biodiversity through cascading trophic systems and negatively impact large-scale ecosystem processes. This is particularly relevant in grassland ecosystems, where in undisturbed systems grasses, forbs, and legumes coexist in diverse communities. Previous studies have explored the hypothesis that loss of plant species negatively impacts biodiversity of other trophic groups and can diminish whole ecosystem functions. In this study we tested how flowering plant species richness influenced arthropod order richness on eight sites in the Grand River Grasslands of south central Iowa, and whether that relationship depended on the vegetation height at which arthropods were sampled. We hypothesized that (1) flowering plant species richness would positively affect arthropod order richness, and that (2) a greater number of arthropod orders would be found 2 centimeters above the ground (hereafter “low”) than 1 meter above the ground (hereafter “high”) at given equal flowering plant species richness. With greater richness of flowering plant species, it is likely that this variety of vegetation supplies a greater amount of habitat available for arthropod communities. Counter to our expectations, flowering plant species richness was not significantly correlated with total arthropod order richness (p = 0.0785). However, richness of “low” arthropod order did increase with an increase in nectar richness (p = 0.0463). Further research including all plant species (rather than merely nectar producing species) and identifying arthropods to a finer taxonomic level may provide more conclusive results supporting our hypotheses. Results of such studies would contribute to the success of biodiversity conservation efforts that focus on bottom-up management practices that can enhance ecosystem functioning at higher trophic levels.